Analisis Manajemen Pengelolaan Wakaf Masjid Raodhatul Jannah Kelurahan Jene Tallasa Kabupaten Gowa - Trisno Wardy Putra; Ahmad Mahdi Bunayya (Al Maal: Journal of Islamic Economics and Banking, 2021)
This study seeks to provide an overview of the management of waqf management at the Raodhatul Jannah mosque, Jene Tallasa Village, Gowa Regency. The not yet certified waqf land can jeopardize the donated land in the future. The quality of human resources for managing mosques is also lacking in quality in developing waqf assets to be more productive. This study aims to provide an overview to the parties involved, in this case waqf, regarding the nature of waqf in Indonesia which has been unproductive and many have not been certified as a consideration for increasing the use of waqf assets in the future. This type of research is descriptive qualitative. The result of this research is the problematic management of waqf in Raodhatul Jannah mosque lies in the land of waqf which is not yet certified due to inevitable obstacles. Most of the mosque managers only run religious and social programs and have not focused on developing waqf assets in a more productive direction.